Immunological role and prognostic value of the SKA family in pan-cancer analysis - Li, Zhengtian; Huang, Lanying; Li, Jiachen; Yang, Wenkang; Li, Weichao; Long, Qiuzhong; Dai, Xinyu; Wang, Hongtao; Du, Gang (Frontiers in Immunology, 2023)
Background The spindle and kinetochore associated (SKA) complex, which plays important roles in proper chromosome segregation during mitosis by maintaining the stabilization of kinetochore-spindle microtubule attachment during mitosis, has recently been reported to exert regulatory effects on the initiation and progression of various human cancer types. Nevertheless, the prognostic significance and immune infiltration of the SKA family across cancers have not been well elucidated. Methods Using data from three large public datasets, including The Cancer Genome Atlas, Genotype-Tissue Expression, and Gene Expression Omnibus databases, a novel scoring system (termed the SKA score) was developed to quantify the SKA family level across cancers. We then evaluated the prognostic impact of the SKA score on survival and assessed the effect of the SKA score on immunotherapy at the pan-cancer level using multiomics bioinformatic analyses. The correlation of the SKA score and the tumor microenvironment (TME) was also explored in depth. Potential small molecular compounds and chemotherapeutic agents were assessed by CTRP and GDSC analyses. Immunohistochemistry was performed to verify the expression of the SKA family genes. Results Our results demonstrated a close correlation between the SKA score and tumor development and prognosis in multiple cancers. The SKA score was positively related to cell cycle pathways and DNA replication across cancers, such as E2F targets, the G2M checkpoint, MYC targets V1/V2, mitotic spindles and DNA repair. Additionally, the SKA score was negatively related to the infiltration of various immune cells with antitumor effects in the TME. In addition, the potential value of the SKA score was identified to predict immunotherapy response for melanoma and bladder cancer. We also demonstrated a correlation between SKA1/2/3 and the response to drug treatment across cancers and the promising potential of the SKA complex and its genes as therapeutic targets in cancer. Immunohistochemistry demonstrated that the expression differences of SKA1/2/3 were significant between the breast cancer group and the paracancerous group. Conclusion The SKA score plays a critical role in 33 cancer types and is highly related to tumor prognosis. Patients with elevated SKA scores have a clear immunosuppressive TME. The SKA score may serve as a predictor for patients receiving anti-PD-1/L1 therapy.